Implikasi Undang-Undang Nomor 32 Tahun 2009 Terhadap Pengaturan Pemanfaatan Sumber Daya Alam Di Desa - Qori Rizqiah H Kalingga; Melvin Serlina Wati Gulo (JUSTITIA : Jurnal Ilmu Hukum dan Humaniora, 2023)
This research was conducted to find out how the implications of Law no. 32/2009 concerning Environmental Protection and Management of the utilization of natural resources in villages. The purpose of this research is to provide a foundation for the village so that the community has a sense of responsibility towards the management and utilization of natural resources in order to ensure the continuity of their supply, so that they will be maintained and increase the quality of the diversity and value of natural resources, especially those in the village. The data used in this study are primary (juridical-normative) and secondary data obtained by observing and documenting. The analysis used is descriptive analysis with the form of qualitative research (socio-legal) and the object studied is Law no. 32/2009 concerning Environmental Protection and Management. Based on the results of the research, it shows that there are arrangements in various laws and regulations related to natural resource management and the concept of village-scale natural resource management is in line with and in accordance with the implications of Law no. 32 of 2009 concerning the Protection and Management of the Environment, but it still needs to be supervised by related parties according to the authority of both the Central Government and the Regional Government, so that the fulfillment of village rights over village-scale natural resources can truly be realized. Therefore it is necessary to regulate technical provisions for monitoring and evaluation as well as providing guidance to villages. Based on the results of the research, it shows that there are arrangements in various laws and regulations related to natural resource management and the concept of village-scale natural resource management is in line with and in accordance with the implications of Law no. 32 of 2009 concerning the Protection and Management of the Environment, but it still needs to be supervised by related parties according to the authority of both the Central Government and the Regional Government, so that the fulfillment of village rights over village-scale natural resources can truly be realized. Therefore it is necessary to regulate technical provisions for monitoring and evaluation as well as providing guidance to villages. Based on the results of the research, it shows that there are arrangements in various laws and regulations related to natural resource management and the concept of village-scale natural resource management is in line with and in accordance with the implications of Law no. 32 of 2009 concerning the Protection and Management of the Environment, but it still needs to be supervised by related parties according to the authority of both the Central Government and the Regional Government, so that the fulfillment of village rights over village-scale natural resources can truly be realized. Therefore it is necessary to regulate technical provisions for monitoring and evaluation as well as providing guidance to villages. 32 of 2009 concerning the Protection and Management of the Environment, but it still needs to be supervised by related parties according to the authority of both the Central Government and the Regional Government, so that the fulfillment of village rights to village-scale natural resources can truly be realized. Therefore it is necessary to regulate technical provisions for monitoring and evaluation as well as providing guidance to villages. 32 of 2009 concerning the Protection and Management of the Environment, but it still needs to be supervised by related parties according to the authority of both the Central Government and the Regional Government, so that the fulfillment of village rights over village-scale natural resources can truly be realized. Therefore it is necessary to regulate technical provisions for monitoring and evaluation as well as providing guidance to villages.